Enhancing Nutrients Knowledge during Pregnancy through Webinars to Prevent Stunting - Bachnas, Muhammad Adrianes; Sulistyowati, Sri; Yuliantara, Eric Edwin; Anggraini, Nutria Widya Purna; Prabowo, Wisnu; Respati, Supriyadi Hari; Nurinasari, Hafi; Ridwan, Robert; Astetri, Lini; Yuliani, Saffana Oka; Carissa, Dinda; Alamsyah, Meuthia (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Indonesia still has a high stunting rate, 1.2 million out of 5 million births each year result in stunted baby growth. linear growth in utero, the process can be caused by maternal malnutrition, which can result in intrauterine growth inhibition and low birth weight, and result in stunting. This study aims to analyze the effectiveness of the webinar in improving nutrition knowledge during pregnancy to prevent stunting growth. Subjects and Method: This is a cross sectional study conducted in July, 15th 2022 using the Zoom Meeting webinar platform. Target population are all young POGI and POGI Members who took part in webinars and online conversations using the Zoom Meeting program. This study used random sampling, and sample size are 161. The independent variables of this study was learning via webinars while the dependent variable was nutrient knowledge. Data were analyzed by paired t-test statistical test. Results: There was a significant difference score of knowledge in pregnant women after (Mean= 8.60) compared to before webinars (Mean= 6.52). Conclusion: The result of this study indicates that learning method via webinars increased maternal understanding about optimal nutrient during pregnancy. Keywords: stunting, nutrients, webinar, pregnant women Correspondence: Nutria Widya Purna Anggraini. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/Dr. Moewardi General Hospital, Surakarta, Central Java, Indonesia. Jl. Kolonel Sutarto No. 132 Jebres, Surakarta. Email: nutria_dr@staff.uns.ac.id. Mobile: 08122651819.